First description of the deutonymphal stage of Laelaps mazzai (Mesostigmata: Laelapidae) - Mario Espinoza-Carniglia; Marcela Lareschi (Persian Journal of Acarology)
The deutonymphal stage of Laelaps mazzai Fonseca, 1939 was described and figured for the first time based on specimens collected from the cricetid rodent Calomys fecundus (Thomas, 1926) from Salta Province, Argentina. The species was originally described on the bases of one female and three males collected from a “wild rat” captured at an unspecified locality of the same province. Herein, the deutonymph share diagnostic characteristics with females and males of L. mazzai, like the hypertrichous condition and the arrangement of setae in the dorsal shield, as well as the chaetotaxy of the coxae. Those characteristics also distinguished L. mazzai from other deutonymphs of Laelaps.